prove sec^4 theta - sec^2theta = tan ^4theta + tan ^2 theta.
Answers
Answered by
7
sec^4 theta - sec^2 theta
= sec^2 theta ( sec^2 theta - 1 )
Now, 1+tan^2 theta = sec^2 theta
Therefore sec^2 theta - 1 = tan^2 theta
So, sec^2 theta ( sec^2 theta -1)
=( tan^2 theta +1) (tan^2 theta)
= tan^4 theta + tan^2 theta
Hence,proved.
= sec^2 theta ( sec^2 theta - 1 )
Now, 1+tan^2 theta = sec^2 theta
Therefore sec^2 theta - 1 = tan^2 theta
So, sec^2 theta ( sec^2 theta -1)
=( tan^2 theta +1) (tan^2 theta)
= tan^4 theta + tan^2 theta
Hence,proved.
Similar questions